Shorter Scleral Spur in Eyes With Primary Open-Angle Glaucoma - Swain, David L. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. We determined whether the scleral spur is shorter in primary open-angle glaucoma (POAG) eyes compared to age-matched normal eyes and whether the collapse of Schlemm's canal (SC) is more prevalent in eyes with a shorter scleral spur. METHODS. The anterior segments of normal (n = 20) and POAG eyes (n = 20) were fixed and processed for light microscopy. The scleral spur length, ratio of posterior trabecular meshwork (TM) insertion into the scleral spur to the posterior TM height, and the percentage of SC collapse were measured. Analysis using an existing mathematical model was conducted to estimate the distances that the scleral spur theoretically would move in vivo and to determine if these distances would be sufficient to keep SC open in POAG compared to normal eyes. RESULTS. The mean scleral spur length was significantly shorter in POAG eyes compared to normal eyes (P < 0.0001). A higher mean percentage of SC collapse was found in POAG eyes than in normal eyes (P < 0.0001). Estimated posterior movement of scleral spur in POAG eyes was less than sufficient to prevent the collapse of SC. A significant negative correlation was found between the posterior scleral spur movement and percent collapse of SC (P < 0.0001). CONCLUSIONS. A shorter scleral spur found in POAG eyes was associated with a higher percent of SC collapse. Our data suggest that a shorter scleral spur may be a risk factor in the development of POAG by being insufficient to hold SC open.